If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 3 = 5 Reorder the terms: 3 + 2y = 5 Solving 3 + 2y = 5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2y = 5 + -3 Combine like terms: 3 + -3 = 0 0 + 2y = 5 + -3 2y = 5 + -3 Combine like terms: 5 + -3 = 2 2y = 2 Divide each side by '2'. y = 1 Simplifying y = 1
| z^2-8iz-16=0 | | 7c-3c=2c+24 | | 96-4y=84 | | 4+7n=n/6 | | 9q=99 | | y/7=.25 | | s-20=33 | | 23*x=46 | | 3-20=33 | | (3x+7)/7=4 | | z^2-8z-5p=0 | | a=8.34fc | | 2(y-3)=-3 | | 7x-3x^2=85+2x^2+2x | | 5-4m=17 | | 5(w+2)=3(w+6) | | 16x^2-7x=17x-9 | | z^2-8iz-5p=0 | | 7x+y=-4 | | 5x^2+40x+100=25 | | 5(x-17)=2(x-3) | | 2X^3+6X^2-2x=0 | | A=s | | 3x^2+12x=131-2 | | 3x^5+12x=131-2 | | 23x+34=23-12x-7x | | b^2+9b+10=-8 | | -9.4x=-65.8 | | 12*(2-x)=25x | | -16.9x=-84.5 | | 6.3x=-88.2 | | 3.9=11.31 |